Konsep Layanan Responsif bagi Siswa yang Mengalami Kesulitan Belajar secara Daring Dimasa Pandemi Covid-19 - Habiba, Bella; Mulyani, Sri; Nia, Nia Ifa; Nugroho, Puspo (IAIN Kudus, 2020)
The Concept Of Responsive Service For Students Who Have Difficulty Learning Online In The Pandemic Covid-19.This study aims to determine the concept of responsive services for students who have difficulty learning online in the pandemic covid-19 era. The method used in this study is a qualitative method with a descriptive approach that discusses the responsive service of BK Teachers as counselors in overcoming online student learning difficulties amid covid-19 outbreaks. The results showed that students' learning difficulties when studying at home online were inadequate facilities and internet networks, lack of understanding of certain subjects and a less conducive atmosphere of learning at home. In research the responsive service strategy used is individual counseling, and collaboration with subject teachers and involving parents. The role of the BK teacher in overcoming learning difficulties is by collecting data, determining diagnosis, prognosis and treatment and evaluation.Keywords: Responsive Service, Learning Difficulties, Online Learning